Energetic demands of training with young gymnastic talents - Irurtia, A.; Gutierrez, J.; Marina, M.; Galilea, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The bioenergetic research in artistic gymnastics (GA) is conditioned by the intrinsic characteristics of a technical combining sport where the variability factors in performance are higher and more complex than in performance sports (Martos, 1991; Bale & Goodway, 1990). The physiologic profile of the elite gymnast has evolved toward higher anaerobic power, VO2max, HR and energetic cost (Jemni et al., 2000, 2001). The increase in time and number of difficulties during the competitive routines seems to be the main reason of this evolution. Even though the energetic demands have been described extensively during competitive routines in adults (Montgomery & Beaudin, 1982), very few studies are oriented toward the energetic demands during the training, especially in young beginners. The aim of this study is to describe the energetic demands in young gymnasts during ordinary training sessions. Methods Five male gymnasts in prepuberal age (10-12 years old) took part in the study. All of them had a background of 30 months of training with microcycles composed of 6 sessions and 20 h per week. The HR was monitored (Polar® Accurex Plus) during 2 weeks of training with the same orientation and structure (close to a general preparatory period). At the end of this period the Course Navette was done to estimate the Vo2max after 2 pre-tests and 8 weeks of running at different paces to familiarize the group. The caloric expenditure was calculated from the relation FC-VO2max with an acceptance of an overestimate of 10-15% (Astrand & Rodahl, 1977; Bunc & Petrizilkova, 1994). Results The HRmean (125 ± 4.8 b/min) registered during the training corresponds to the 71% of the HRmax (177 ± 4.9 b/min) monitored in the gymnasium and to the 63% of the HR (198 ± 7.6 b/min) obtained in Course Navette. The values, classified in blocks, are shown in Table 1. The mean VO2 (20.5 ± 3.3 ml/kg/min) in training corresponds to the 40% of the VO2max (51.6 ± 1.3 ml/kg/min) estimated in Course Navette (Table 2). The mean caloric expenditure during training was 221 Kcal/h. Discussion/Conclusion In spite of the recognized limitations in using the relation FC - VO2 to measure the training load in AG (Jemni et al., 2000; Bunc & Petrizilkova, 1994; Rodríguez et al., 1999; Astrand & Rodahl, 1977), it is still the most used method to measure the load in training and competition (Rodríguez et al., 1999). The absence of studies with subjects with a similar profile to our gymnasts does not allow comparisons. The higher HRmax in trampoline (171 b/min) in comparison to those of strength (161 b/min) may reveal the influence of emotional factors, which reach very high levels in acrobatics and aerial executions. The maximal values of the HRmean are registered in vault (139 b/min), which is characterized by work blocs of short duration executions. This observation contradicts results of other studies (Jemni et al., 2000; Rodríguez et al., 1999), where the lowest maximal and mean values are located precisely in vault. The differences could be explained by the different training nature and orientation of adult gymnasts in competition routines (maximal difficulties and more recovery) in comparison to young gymnasts (basic elements and short recovery). Our results suggest the interest of more research with young gymnasts.